Step up Eketahuna LLC ; Summit Entertainment ; Touchstone Pictures ; produced by Erik Feig, Jennifer Gibgot, Adam Shankman, Patrick Wachsberger ; story by Duane Adler ; screenplay by Duane Adler and Melissa Rosenberg ; directed by Anne Fletcher. - Tatum, Channing 1980-.; Fletcher, Anne 1966-.; Dewan, Jenna 1980-.; Radcliff, Damaine 1979-.; Washington, De'Shawn.; Seresin, Michael 1942-.; Zigman, Aaron 1963-.; Touchstone Home Entertainment (Firm).; Buena Vista Home Entertainment (Firm).; D'Concorde Recording Corporation ([Quezon City] D'Concorde Recording Corp., 2006)
Tyler is a rebel from the wrong side of Baltimore¹s tracks. The only thing that stands between him and an unfulfilled life are his dreams of one day making it out of there. Nora is a privileged ballet dancer attending an elite school of dance in Baltimore. The only thing standing in the way of her brilliant future is finding a great dance partner for her senior showcase. When trouble with the law lands Tyler with a community service gig at Maryland School of the Arts, he arrives as an angry outsider, until his skills as a gifted street dancer draw Nora¹s attention. With sparks flying on and off stage, Tyler realizes he has just one performance to prove that he can step up to a life far larger than he ever imagined.
Special features: Deleted scenes; Bloopers; MySpace.com dance contest videos; "Making the moves" featurette; Music videos.
Title from container.
Director of photography, Michael Seresin ; editor, Nancy Richardson ; music, Aaron Zigman ; costume designer, Alix Hester ; production designer, Shepherd Frankel.
Channing Tatum, Jenna Dewan, Damaine Radcliff, De'Shawn Washington, Mario, Drew Sidora, Rachel Griffiths, Josh Henderson, Tim Lacatena.
DVD; region 1; widescreen (2.35:1, enchanced) presentation.
Keywords: Dancers -- Maryland -- Baltimore -- Drama; High school students -- Conduct of life -- Drama; Community service (Punishment) -- Maryland -- Baltimore -- Drama; Melodrama, American; Feature films; Melodrama; Musical films; Films for the hearing impaired; Musical; Romance; Youth; Drama